2014
DOI: 10.1016/j.celrep.2014.04.051
|View full text |Cite
|
Sign up to set email alerts
|

A Presynaptic Role for the Cytomatrix Protein GIT in Synaptic Vesicle Recycling

Abstract: Neurotransmission involves the exo-endocytic cycling of synaptic vesicles (SVs) within nerve terminals. Exocytosis is facilitated by a cytomatrix assembled at the active zone (AZ). The precise spatial and functional relationship between exocytic fusion of SVs at AZ membranes and endocytic SV retrieval is unknown. Here, we identify the scaffold G protein coupled receptor kinase 2 interacting (GIT) protein as a component of the AZ-associated cytomatrix and as a regulator of SV endocytosis. GIT1 and its D. melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 37 publications
4
38
1
Order By: Relevance
“…In coimmunoprecipitations from P2 fractions of mouse brains, RIM-BP2 coprecipitated with RIM and Munc13-1, but not with the Arf GTPase-activating protein GIT, a binding partner of Piccolo (9) and of endocytotic proteins such as Dynamin1 (Fig. S1E) and Stonin 2 (10). Together, these results indicate that RIM-BP2 is part of the presynaptic AZ scaffold and forms a complex with the priming factors RIM and Munc13-1.…”
Section: Resultssupporting
confidence: 53%
“…In coimmunoprecipitations from P2 fractions of mouse brains, RIM-BP2 coprecipitated with RIM and Munc13-1, but not with the Arf GTPase-activating protein GIT, a binding partner of Piccolo (9) and of endocytotic proteins such as Dynamin1 (Fig. S1E) and Stonin 2 (10). Together, these results indicate that RIM-BP2 is part of the presynaptic AZ scaffold and forms a complex with the priming factors RIM and Munc13-1.…”
Section: Resultssupporting
confidence: 53%
“…Moreover, genome-wide association studies have identified single nucleotide polymorphisms (SNPs) in the genes encoding for the AP180 paralog CALM, dynamin 2, and amphiphysin 1 in familial and sporadic cases of Alzheimer's disease (Aidaralieva et al, 2008;Harold et al, 2009;Seshadri et al, 2010). Finally, GIT1 (termed dGIT in Drosophila), an AZ-associated scaffold with GTPase activating protein activity toward Arf6, associates with stonin 2/stoned B and regulates SV recycling (Podufall et al, 2014). Human mutations in GIT1, which is also found postsynaptically, are associated with attention deficit hyperactivity disorder (ADHD) and cause ADHD-like phenotypes in GIT1 mutant mice (Won et al, 2011).…”
Section: Perspectivesmentioning
confidence: 99%
“…The release of neurotransmitter vesicles is restricted to the presynaptic active zone through a macromolecular complex called the presynaptic cytoplasmic matrix or cytomatrix (Gundelfinger and Fejtova, 2012). GIT1, in complex with β-PIX and paxillin, binds the cytomatrix proteins piccolo and stonin-2 (Podufall et al, 2014) to regulate localized neurotransmitter vesicle release and reuptake. In Drosophila, dGIT interacts with stoned B at the periphery of the synaptic active zone, and dgit mutant flies have defective synaptic vesicle recycling (Podufall et al, 2014).…”
Section: Functions In the Nervous Systemmentioning
confidence: 99%
“…GIT and PIX each bind partner proteins that localize the complex to specific cellular locations. These proteins include the GIT partners paxillin (to focal adhesions; Turner et al, 1999), piccolo and stonin-2 (to presynaptic active zones in neurons; Kim et al, 2003;Podufall et al, 2014) and liprin-α (to postsynaptic membranes; Ko et al, 2003), as well as the β-PIX PDZ partners scribble (to epithelial cell-cell contacts and synapses; Audebert et al, 2004;Richier et al, 2010) and shank (to postsynaptic membranes; Park et al, 2003).…”
Section: Git Proteinsmentioning
confidence: 99%
See 1 more Smart Citation